Danger UXB the heroic story of WWII bomb disposal teams - Owen, James 1969- (Little, Brown, 2010)
Autumn 1940: the Front Line is now Britain itself. With invasion imminent, cities are blitzed nightly as for the first time a nation becomes the target of a campaign of aerial assault. And even after the planes have passed overhead, a deadly menace remains: thousands upon thousands of unexploded bombs. Buried under ground, their clocks ticking remorselessly, UXBs blocked supply routes, closed Spitfire factories and made families into refugees. Dealing with this threat soon became Churchill's priority. For the first time, Danger UXB reveals the story of this desperate struggle against the ticking clock. It was a battle of wits that pitted German ingenuity against British resourcefulness, told through four key figures in the new science of bomb disposal: Robert Davies GC, who saved St Paul's Cathedral; Stuart Archer GC, protector of the vital Welsh oil refineries; the extraordinary Earl of Suffolk GC; and John Hudson GM, the horticulturalist who mastered the V1. An astonishing and compelling account of courage and self-sacrifice, this is the truth of how the Blitz was beaten.